Optimal monitoring to implement clean technologies when pollution is random - Inés Macho-Stadler; David Pérez-Castrillo (SERIEs - Journal of the Spanish Economic Association, 2010)
We consider a model of polluting firms subject to tax on emissions, monitoring, and penalties in case of underreporting and which face a choice between a more expensive clean and a less expensive dirty technology. Moreover, emissions are subject to random events.We show that the optimal monitoring is a cut-off policy, where all reports below a threshold are inspected with the same probability, while reports above the threshold are not monitored. If the adoption of the technology is firms' private information, too few firms will adopt the clean technology under the optimal monitoring policy. However, when the environmental agency can check the technology adopted by the firms, the optimal policy may induce overswitching or underswitching to the clean technology.
Keywords: K32; K42; D82; 330; production technology; random emissions; environmental taxes; optimal monitoring policy; Umweltpolitik; Kontrolle; Umweltbelastung; Fertigungstechnik; Technologiewahl; Umweltschutz; Ökosteuer; Theorie